Well‐being of higher education consumers: A review and research agenda - Khatri, Puja; Duggal, Harshleen Kaur (International journal of consumer studies, 2022)
The concept of students‐as‐consumers has gained traction with the neo‐liberal agenda taking root in the higher education arena. A key value that these consumers look for and derive from their tertiary education is well‐being. Thus, a cognizance of the nature of student well‐being (SWB) is vital for educational institutions to effectively foster the well‐being of their consumers. This calls for synthesizing existing literature to facilitate an aggregate understanding of the construct. This review paper aims to integrate the bulk of psychological, higher education and consumer literature on well‐being of students to arrive at a holistic picture. To achieve this, a framework‐based systematic review of 112 articles from the last two decades was conducted. A combination of two well‐established organizing frameworks has been used to generate structured insights. The antecedents, decisions and outcomes (ADO) framework reveals what we know about the construct. Simultaneously, the theories, contexts and methods (TCCM) framework sheds light on the different theories, contexts and methods applied in SWB research. Additionally, this paper also strives to uncover the major gaps in extant literature and provide concrete directions for future research. Scholars across the disciplines of psychology, marketing and consumer behaviour can draw on these findings and directions for conducting their research. Because the review was undertaken from a global standpoint, it has implications for researchers and practitioners across the world. Higher education institutes can use these findings to develop support mechanisms that will allow them to fulfil their pastoral role to student consumers and inculcate a positive brand image.